CSR disclosure in response to major airline accidents: a legitimacy-based exploration. Issue 1 (7th March 2016) - Vourvachis, Petros; Woodward, Thérèse; Woodward, David G.; Patten, Dennis M
Abstract : Purpose: – The purpose of this paper is to contribute to the literature investigating disclosure reactions to legitimacy threats by analyzing the corporate social responsibility (CSR) disclosure reactions to catastrophic accidents suffered by major airlines. Design/methodology/approach: – The authors use content analysis to examine changes in annual report disclosure in response to four separate airline disasters. The authors adopt two classification schemes and two measurement approaches to explore these changes. Findings: – The authors find that for three events the organizations appear to have responded with considerable increases in CSR disclosure that are consistent with attempts of legitimation. For one of the events examined, the authors find no disclosure response and suggest that this could be due to the company's unwillingness to accept responsibility. Research limitations/implications: – The study's focus on major airlines that have suffered an accident with available annual reports in English meant that other companies had to be excluded from the analysis. Practical implications: – The findings demonstrate the use of the annual report as a legitimation tool and further highlight the need for greater transparency and comparability across publications. Originality/value: – The paper adds to the scarce literature examining corporate disclosure reactions following threats to their social legitimacy.